Stroke subtypes in southern Iran: - Safari, Rasool; Borhanihaghighi, Afshin; Heydari, Seyed Taghi; Safari, Anahid; Cruz-Flores, Salvador (Galen Medical Journal, 2015)
Objective: To investigate about frequency of different subtypes of stroke in south of Iran Methods: This is a retrospective, single-center study conducted at Namazi Hospital, Shiraz, south of Iran. Age, sex, length of hospitalization and mortality of stroke patients were recorded by reviewing hospital medical records. Results: 16 351 patients (53.6% male, 46.4%female) were recruited. Ischemic stroke (10750 patients, 65.7%), intracerebral hemorrhage(3282 patients,20.1%) and subarachnoid hemorrhage(1057 patients,6.5%) were the most common subtypes of stroke, respectively. In 1262 patients (7.7%) the stroke subtype could not been specified. Ischemic stroke and intracerebral hemorrhage were more common in men but subarachnoid hemorrhage was more common in women. Subarachnoid hemorrhage occurred significantly in younger patients. Mortality was significantly higher in intracerebral hemorrhage. Hospital stay was significantly longer in subarachnoid hemorrhage group. Conclusion: the distribution of the different subtypes of stroke in Iran is similar to Caucasians.